Pengembangan Instrumen Diagnostik Three Tier Test pada Materi Pecahan Kelas VII - Lu’lu Yu’tikan Nabilah; Ruslan; Rusli (Issues in Mathematics Education (IMED), 2019)
This study aims to produce a three tier diagnostic test instrument of fraction topic for grade VII that feasible and valid, determine the feasibility of the instrument based on validity, reliability, and degree of difficulty, and reveal the misconceptions experienced by class VII students on fraction topic. This type of research is research and development. Research subjects from essay test trials, open-reasoned multiple choice tests, until the application of the three tier test instruments will be tested on students of class VII. The research procedure starts with a preliminary study, drafting a product, until product development is continued with the analysis of three tier tests in terms of validity, reliability, and the level of difficulty and analysis and interpretation of misconceptions from the results of the three tier test. The results of the study were obtained (1) the three tier test diagnostic instruments used to identify misconceptions in fraction number material were developed through preliminary study stages, designing essay tests, designing multiple choice tests, up to three tier tests; (2) the three tier tests developed meet the criteria of valid, reliable, and with a difficulty level of 6.7% easy, 26.7% medium, and 66.6% difficult; (3) students experience misconceptions on indicators explaining fraction definitions, comparing fractions of numbers, and calculating addition, subtraction, multiplication, and fraction division operations.